Uterine myoma postoperative anti-adhesion absorbable membrane and preparation method thereof

By embedding siRNA nanocomposites targeting TGF-β1 and Smad3 in an absorbable anti-adhesion membrane after uterine fibroid surgery, and utilizing a dynamic covalent cross-linking network composed of aldehyde-modified hyaluronic acid and catechol-functionalized gelatin, the time-sequential release of siRNA is achieved, synergistically inhibiting the TGF-β1/Smad pathway, thus solving the problem of postoperative tissue adhesion and achieving a highly efficient adhesion prevention and treatment effect.

CN121288028APending Publication Date: 2026-01-09ANKANG CENT HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511810305.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-03
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Postoperative tissue adhesions are a common complication of uterine fibroid removal surgery, leading to problems such as chronic pain, secondary infertility, and intestinal obstruction. Current technology is unable to effectively block the fibrosis signaling pathway, resulting in adhesions and recurrence.

Method used

A dynamic covalent cross-linked network composed of aldehyde-modified hyaluronic acid and catechol-functionalized gelatin was used to encapsulate siRNA nanocomposites targeting TGF-β1 and Smad3. The time-sequential release of siRNA was achieved through different cationic polymers, synergistically inhibiting the TGF-β1/Smad pathway.

Benefits of technology

It significantly reduces the incidence of postoperative adhesions and recurrence rates. Through dual gene targeting synergy and time-series controlled release technology, it almost completely blocks fibrosis signals. The material is self-healing, wet-adhesive, and controllable degradable under physiological conditions, and has no immunogenicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121288028A_ABST
    Figure CN121288028A_ABST
Patent Text Reader

Abstract

The invention discloses a hysteromyoma postoperative anti-adhesion absorbable film and a preparation method thereof, and belongs to the technical field of biomedical materials. The membrane is prepared from hydroformylated hyaluronic acid, catechol functionalized gelatin, a siTGF-beta1 / LMWC nano-composite and a siSmad3 / PEI nano-composite through a dynamic covalent cross-linking and gene sequential controlled release technology. A-HA and C-Gel are subjected to a Schiff base reaction to form a dynamic crosslinking matrix with self-healing, wet adhesion and controllable degradability; the siTGF-beta1 and the siSmad3 respectively target an upstream switch and a central hub of a TGF-beta1 / Smad pathway, and time sequence release is realized by means of the characteristic difference between the LMWC and the PEI. An in-vitro experiment proves that the inhibition rate gt of the membrane on a fibroblast fibrosis marker is gt; the effect can be maintained for 28 days, the biocompatibility is excellent, the clinical operation is convenient, the postoperative adhesion is prevented from the molecular source, the defects of single target spot and short effect in the prior art are overcome, and the clinical application value is great.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to an absorbable biomembrane with active gene therapy function. It is particularly suitable for the prevention of adhesions between the uterus and surrounding tissues (such as intestines, fallopian tubes, and ovaries) during gynecological surgeries such as uterine fibroid and adenomyosis. It can also be extended to surgical scenarios with high incidence of postoperative tissue adhesions, such as abdominal and orthopedic surgeries. The core feature is that it blocks the fibrosis process from the molecular level through dual gene targeting synergy and time-controlled release technology. Background Technology

[0002] Uterine fibroids are the most common benign tumors of the female reproductive system, with an incidence rate as high as 20%-30%. Currently, surgical removal, such as laparoscopic or open myomectomy, is the main treatment for this disease. However, postoperative tissue adhesions are a common and frequent complication of such surgeries, with an incidence rate exceeding 60%. Severe postoperative tissue adhesions can lead to a series of problems for patients, including chronic pelvic pain (incidence rate 30%-40%), secondary infertility (approximately 15%), intestinal obstruction (approximately 5%), and increased difficulty in repeat surgeries, causing patients significant physical suffering and a heavy economic burden.

[0003] Postoperative adhesions are essentially a form of "hyperfibrosis" during wound healing. Specifically, the surgical wound activates the body's inflammatory response, leading to the proliferation and migration of fibroblasts and the secretion of excessive collagen, resulting in abnormal fibrous connective tissue and ultimately pathological adhesions between adjacent tissues. In this process, the TGF-β1 / Smad signaling pathway is considered the core molecular mechanism regulating this hyperfibrosis. TGF-β1, acting as the "upstream switch" of this pathway, can be activated by the inflammatory microenvironment of the wound via autocrine or paracrine signals, subsequently binding to corresponding receptors on the fibroblast membrane. Once activated, the receptors are phosphorylated, further activating Smad2 / 3 proteins, with Smad3 considered the "central hub." Phosphorylated Smad3 forms a complex with Smad4 and enters the cell nucleus, regulating the gene expression of fibrosis markers such as collagen I and α-smooth muscle actin (α-SMA), ultimately leading to fibroblast differentiation into myofibroblasts, excessive collagen deposition, and the formation of adhesion tissue. Summary of the Invention

[0004] This invention provides an absorbable membrane for preventing adhesions after uterine fibroid surgery, capable of synergistically inhibiting fibrosis signaling pathways at the molecular level. This membrane achieves the dual functions of a physical barrier and active gene therapy, significantly reducing the incidence and recurrence rate of postoperative adhesions.

[0005] This invention provides an absorbable anti-adhesion membrane for uterine fibroid surgery, prepared from raw materials containing the following components: Aldehyaluronic acid with an aldehyde degree of 15%-30%; Catechol-functionalized gelatin with a grafting rate of 8%-20%; A first nanocomposite formed by siRNA (siTGF-β1) targeting the TGF-β1 gene and a first cationic polymer; A second nanocomposite is formed by siRNA (siSmad3) targeting the Smad3 gene and a second cationic polymer.

[0006] In this membrane, aldehyde-modified hyaluronic acid with an aldehyde degree of 15%-30% and catechol-functionalized gelatin with a catechol grafting rate of 8%-20% form a dynamic covalent cross-linked network through a Schiff base reaction between the aldehyde and amino groups, constituting the membrane matrix; the first nanocomposite and the second nanocomposite are embedded and fixed in the dynamic cross-linked network. Furthermore, this postoperative anti-adhesion absorbable membrane for uterine fibroid surgery achieves the time-sequential release of siTGF-β1 and siSmad3 through the difference in properties between the first and second cationic polymers.

[0007] This invention creatively selects two key and functionally complementary genes in the TGF-β1 / Smad pathway as targets. siTGF-β1 reduces the "upstream signaling source," while siSmad3 blocks the "downstream transmission pathway." Even if a small amount of uninhibited TGF-β1 exists, its signal cannot be transmitted through Smad3. The synergistic inhibitory effect achieved by siTGF-β1 and siSmad3 almost completely blocks fibrosis signaling.

[0008] siTGF-β1 silences the mRNA of TGF-β1 (GenBank accession number: NM_000660.7) at the upstream end of the pathway, reducing the synthesis and secretion of pro-fibrotic cytokines and achieving "upstream interception". The sense strand sequence of siTGF-β1 is SEQ ID NO:1 (5'-GCAACAACGCCAUCAUAGAACdTdT-3'), and the antisense strand sequence is 5'-GUUCUAUGAUGGCGUUGUUGCdTdT-3' (SEQ ID NO:2). This sequence has been specifically verified to have a silencing efficiency of ≥90% for the TGF-β1 gene and no off-target effects.

[0009] siSmad3 silences the mRNA of Smad3 (GenBank accession number: NM_005902.3), the "central hub" of signal transduction, blocking the expression of all downstream fibrosis genes mediated by Smad3, thus achieving "central blockade." The sense strand sequence of siSmad3 is SEQ ID NO:3: 5'-GGAACAAGGAGUUCUUCUAdTdT-3'; the antisense strand sequence is SEQ ID NO:4: 5'-UAGAAGAACUCCUUGUUCCdTdT-3', with a silencing efficiency ≥92% and high specificity.

[0010] As the raw material for the membrane, the first cationic polymer is low molecular weight chitosan (LMWC) with a molecular weight ≤10kDa, and the mass ratio of siTGF-β1 to LMWC is 1:10 to 1:50. As the raw material for the membrane, the second cationic polymer is branched polyethyleneimine (PEI) with a molecular weight of 25 kDa, and the N / P ratio of siSmad3 to PEI is 5:1 to 15:1.

[0011] This invention constructs a time-release system by combining cationic polymers with different properties with two different siRNAs to match the postoperative fibrosis process. Details are shown in Table 1 below.

[0012] Table 1 The complex formed by LMWC and siRNA through electrostatic interactions has a loose structure and interacts weakly with the negatively charged hyaluronic acid network in the matrix, facilitating rapid diffusion and release. PEI's proton sponge effect (buffering lysosomes to pH below 5.0, causing lysosomal rupture and escape of the nanocomplex) not only improves transfection efficiency, but its complex with siRNA also exhibits stronger hydrophobic interactions, a more compact structure, and more significant electrostatic interactions with the hyaluronic acid network, resulting in slower release.

[0014] In addition, the present invention uses aldehyde-modified hyaluronic acid and catechol-functionalized gelatin to construct a dynamic covalent cross-linked network through Schiff base reaction, which serves as the matrix of the membrane, giving the matrix network properties.

[0015] The matrix exhibits dynamic reversibility. Schiff base bonds (-N=C-) can dynamically break and recombine under physiological conditions, endowing the material with self-healing capabilities (complete healing within 10 minutes after incision), ensuring the integrity of wound coverage.

[0016] The substrate exhibits wet adhesion. The catechol groups can be oxidized in a moist environment to form a quinone structure, which covalently binds to the amino and thiol groups on the tissue surface. At the same time, the adhesion is enhanced through hydrogen bonding and hydrophobic interactions, with an adhesion strength of 18.5±2.1 kPa, allowing it to adhere firmly to irregular wound surfaces.

[0017] The substrate is controllable and degradable. Degradation relies on the enzymatic action of hyaluronidase and collagenase in the body, and it can be completely degraded within 28 days. The degradation products are hyaluronic acid and gelatin (both natural components of the human body), which are non-immunogenic and do not require secondary surgery for removal.

[0018] The matrix has a porous structure. After freeze-drying, a porous structure with a pore size of 100±50μm is formed, which is conducive to the exchange of nutrients and cells.

[0019] This invention provides a method for preparing an absorbable anti-adhesion membrane after uterine fibroid surgery, comprising the following steps: Prepare aqueous solutions of aldehyde-modified hyaluronic acid and catechol-functionalized gelatin; A first nanocomposite was prepared by combining siRNA (siTGF-β1) targeting the TGF-β1 gene with a first cationic polymer; A second nanocomposite was prepared by combining siRNA (siSmad3) targeting the Smad3 gene with a second cationic polymer; Add the first nanocomposite and the second nanocomposite to the catechol-functionalized gelatin aqueous solution, and then mix with an equal volume of aldehyde-modified hyaluronic acid aqueous solution. Vortex the mixture to allow A-HA and C-Gel to undergo a Schiff base reaction through the aldehyde and amino groups. Pour the mixture into a mold and let it stand at 37°C for 15-30 minutes to form a hydrogel. The hydrogel can be freeze-dried to form the absorbable anti-adhesion membrane after uterine fibroid surgery.

[0020] Furthermore, the concentration of the aldehyde-modified hyaluronic acid aqueous solution is 3%-6% (w / v), preferably 4% (w / v). For example, it is prepared using PBS buffer at pH 7.4.

[0021] Furthermore, the concentration of the catechol-functionalized gelatin aqueous solution is 3%-6% (w / v), preferably 4% (w / v). For example, it is prepared using PBS buffer at pH 7.4.

[0022] Further, 10-20 μg / mL of the solution formed in the first nanocomposite and the second nanocomposite is added to the catechol-functionalized gelatin aqueous solution.

[0023] Furthermore, in the preparation of the first nanocomposite, siTGF-β1 and LMWC are mixed at a mass ratio of 1:10 to 1:50. In the preparation of the second nanocomposite, siSmad3 and PEI are mixed at an N / P ratio of 5:1 to 15:1.

[0024] Specifically, under sterile conditions, an aqueous solution of aldehyde-modified hyaluronic acid is mixed with an equal volume of drug-loaded C-Gel aqueous solution of the first nanocomposite and the second nanocomposite, and vortexed for 5-10 minutes to allow the aldehyde-modified hyaluronic acid and catechol-functionalized gelatin to undergo a Schiff base reaction through the aldehyde and amino groups. The total polymer concentration of the mixture is controlled at 3%-6% (w / v), preferably 4% (w / v).

[0025] Specifically, the mixture is injected into a sterile mold and allowed to stand at 37°C for 15-30 minutes to allow the reaction to proceed fully and form a hydrogel membrane. The obtained hydrogel membrane is placed in a freeze dryer and pre-frozen at -80°C for 3-5 hours, and then dried under a vacuum of ≤10Pa for 30-40 hours to obtain a porous absorbable membrane material. The absorbable membrane is then sealed and packaged, and sterilized by cobalt-60 irradiation (dose 20-30kGy, preferably 25kGy) to obtain the finished product.

[0026] Specifically, in preparing the first nanocomposite, LMWC and siTGF-β1 were first dissolved in HEPES buffer (pH=7.2), then the two solutions were mixed, vortexed for 10 min, and then allowed to stand at room temperature for 30 min; in preparing the siSmad3 / PEI nanocomposite, PEI and siSmad3 were first dissolved in sterile enzyme-free water, then the PEI solution was added dropwise to the siSmad3 solution, vortexed for 10 min, and then allowed to stand at room temperature for 30 min. Attached Figure Description

[0027] Figure 1 SEM images of membranes G0 (A), G1 (B), G2 (C), and G3 (D).

[0028] Figure 2 Infrared images of films G0, G1, G2, and G3.

[0029] Figure 3 In vitro release curves of siRNA from membranes of G0, G1, G2, and G3.

[0030] Figure 4 Results of COL1A1 inhibition rate, ACTA2 inhibition rate, collagen I inhibition rate and α-SMA inhibition rate of G0, G1, G2 and G3 membranes.

[0031] Figure 5 Healing rate curves of cell scratch experiments on G0, G1, G2, and G3 membranes. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Reagents not specifically described in detail in this invention are all conventional reagents and are commercially available; methods not specifically described in detail are all conventional experimental methods and can be obtained from the prior art.

[0033] Example 1: Preparation of an absorbable anti-adhesion membrane after uterine fibroid surgery 1. Raw material preparation Hyaluronic acid (HA): molecular weight 150kDa, purity ≥98%; Gelatin: derived from pigskin, molecular weight 80kDa; Dopamine hydrochloride, sodium periodate, low molecular weight chitosan (LMWC, 5 kDa), and branched PEI (25 kDa) were all of analytical grade.

[0034] siTGF-β1 silences the mRNA of TGF-β1 (GenBank accession number: NM_000660.7) at the upstream end of the pathway, reducing the synthesis and secretion of pro-fibrotic cytokines and achieving "upstream interception". The sense strand sequence of siTGF-β1 is SEQ ID NO:1 (5'-GCAACAACGCCAUCAUAGAACdTdT-3'), and the antisense strand sequence is 5'-GUUCUAUGAUGGCGUUGUUGCdTdT-3' (SEQ ID NO:2). This sequence has been specifically verified to have a silencing efficiency of ≥90% for the TGF-β1 gene and no off-target effects.

[0035] siSmad3 silences the mRNA of Smad3 (GenBank accession number: NM_005902.3), the "central hub" of signal transduction, blocking the expression of all downstream fibrosis genes mediated by Smad3, thus achieving "central blockade." The sense strand sequence of siSmad3 is SEQ ID NO:3: 5'-GGAACAAGGAGUUCUUCUAdTdT-3'; the antisense strand sequence is SEQ ID NO:4: 5'-UAGAAGAACUCCUUGUUCCdTdT-3', with a silencing efficiency ≥92% and high specificity.

[0036] Aldehyaluronic acid (A-HA) with a degree of aldehyde 25% was prepared by reduction with sodium periodate.

[0037] 2. Preparation of catechol-functionalized gelatin (C-Gel) Dissolve 1g of gelatin in 50mL of PBS buffer (pH=7.4) and stir at 37℃ until dissolved; Add 0.2g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and 0.12g of N-hydroxysuccinimide (NHS) to activate the gelatin carboxyl groups for 30 minutes; Add 0.15g of dopamine hydrochloride (gelatin to dopamine molar ratio 1:0.15), and react at 37℃ for 4h; Dialysis (using a dialysis bag with a molecular weight cutoff of 10 kDa) for 48 hours (with PBS replaced every 8 hours), followed by freeze drying to obtain C-Gel powder. The catechol grafting rate was 15% as determined by ultraviolet spectrophotometry (absorbance at 280 nm).

[0038] 3. Prepare aqueous solutions of aldehyde-modified hyaluronic acid and catechol-functionalized gelatin. Aldehyaluronic acid aqueous solution with pH 7.4 was prepared at a concentration of 4% (w / v). Catechol-functionalized gelatin aqueous solution with pH 7.4 was also prepared at a concentration of 4% (w / v).

[0039] 4. Preparation of the first nanocomposite A 1 mg / mL HEPES buffer solution of LMWC (pH=7.2) and a 20 μg / mL HEPES buffer solution of siTGF-β1 were prepared. The two solutions were mixed at a siTGF-β1 to LMWC mass ratio of 1:20 (total volume 10 mL), vortexed for 10 min (2000 rpm), and allowed to stand at room temperature for 30 min to obtain the first nanocomposite. Dynamic light scattering (DLS) analysis showed that the composite particle size was 120±15 nm, the surface potential was +18±2 mV, and the dispersion index (PDI) was 0.21±0.03, indicating that the composite was uniformly dispersed and had good stability.

[0040] 5. Preparation of the second nanocomposite A mixture of 0.5 mg / mL 25 kDa PEI in sterile, enzyme-free water and 20 μg / mL siSmad3 in sterile, enzyme-free water was prepared. The PEI solution was added dropwise to the siSmad3 solution (total volume 10 mL) at an N / P ratio of 10:1 (molar ratio of the amino group of PEI to the phosphate group of siRNA). The mixture was vortexed for 10 min and allowed to stand at room temperature for 30 min to obtain the second nanocomposite. DLS analysis showed that the composite particle size was 100 ± 12 nm, the surface potential was +27 ± 3 mV, and the PDI was 0.18 ± 0.02, meeting the requirements for a nanomedicine delivery system.

[0041] 6. Forming and freeze-drying of anti-adhesion film Add a first nanocomposite with a final concentration of 15 μg / mL and a second nanocomposite with a final concentration of 15 μg / mL to the catechol-functionalized gelatin aqueous solution, then mix with an equal volume of aldehyde-modified hyaluronic acid aqueous solution, vortex for 5 min, and inject into a polytetrafluoroethylene mold (5 cm in diameter and 0.2 mm in thickness); let stand at 37 °C for 20 min to allow A-HA and C-Gel to undergo a Schiff base reaction to form a hydrogel membrane; freeze-dry (pre-freeze at -80 °C for 4 h, vacuum degree 10 Pa, drying time 36 h) to obtain a porous absorbable membrane product (G0), seal and package, and then sterilize by cobalt-60 irradiation (dose 25 kGy).

[0042] Porous absorbable membrane products with only the first nanocomposite added at a final concentration of 15 μg / mL (G1) and porous absorbable membrane products with only the second nanocomposite added at a final concentration of 15 μg / mL (G2) were used as controls.

[0043] 5. Preparation of the comparative G3 membrane A 1 mg / mL LMWC HEPES buffer (pH=7.2) was prepared and mixed with 20 μg / mL siTGF-β1 and 20 μg / mL siSmad3 HEPES buffers, respectively, to obtain the first and second nanocomplexes of this comparative example. DLS analysis showed that the first nanocomplex had a particle size of 122±14 nm and a surface potential of +17±2 mV; the second nanocomplex had a particle size of 118±13 nm and a surface potential of +18±3 mV. Both had a dispersion index (PDI) <0.25, meeting the requirements for nanocomplexes. The two nanocomplexes were then mixed at a siRNA to LMWC mass ratio of 1:20 (10 mL total volume each), vortexed for 10 min (2000 rpm), and incubated at room temperature for 30 min.

[0044] A first nanocomposite with a final concentration of 15 μg / mL and a second nanocomposite with a final concentration of 15 μg / mL were added to the catechol-functionalized gelatin aqueous solution, and then mixed with an equal volume of aldehyde-modified hyaluronic acid aqueous solution to prepare the comparative G3 film according to the method of the above embodiment.

[0045] like Figure 1 As shown, membranes G0, G1, G2, and G3 all exhibit cross-linked porous structures with pore sizes of 100±50μm, showing no significant differences. The porous structure facilitates siRNA release and nutrient exchange.

[0046] like Figure 2As shown, -OH stretching vibrations appear near 3300 cm⁻¹, with the strongest peak in the G3 membrane (containing PEIMWC) (penetration rate approximately 0.67), and the G0 membrane in between (penetration rate approximately 0.64), reflecting the differences in hydroxyl content among different carriers. Amide I and amide II bands appear at 1650 cm⁻¹ and 1540 cm⁻¹, with the highest peak intensity in the G3 membrane (dual siRNA), followed by the G0 membrane (dual siRNA). CN stretching vibrations (a characteristic peak of PEI) appear near 1380 cm⁻¹, with the strongest peak in the G2 membrane (pure PEI), moderate intensity in the G0 membrane, and weaker intensity in the G3 membrane. Chitosan characteristic peaks appeared around 1150 cm⁻¹ (LMWC carrier, G3 membrane peak was strongest, G1 membrane peak was second strongest, and G0 membrane peak was moderate). Infrared spectroscopy clearly confirmed the unique dual-carrier design of the G0 membrane, containing both LMWC and pure PEI carriers with different properties, in a balanced ratio, providing the structural basis for the time-sequential release of siRNA. The carriers in the G3 membrane were clearly distinguishable from those in the G3 membrane. This structural design is key to the rapid release of siTGF-β1 (approximately 55% at 48h) and the slow release of siSmad3 (approximately 22% at 48h) of the G0 membrane, providing the material basis for subsequent anti-fibrotic effects.

[0047] Example 2: Self-healing performance test 1. Experimental Procedure Take three pieces each of G0, G1, G2, and G3 membranes (each with a diameter of 5 cm, in a dry state) and immerse them in sterile PBS buffer (pH=7.4) for 30 min until fully hydrated (hydration thickness approximately 0.5 mm). Use a sterile scalpel to cut each hydrated membrane in half along its diameter, ensuring the cut surfaces are fully aligned and in contact. Allow them to stand at room temperature (25°C) and record the healing status at 0 min, 5 min, 10 min, and 15 min. At 10 min, lift one end of each membrane with sterile forceps to observe for breakage. If it is not broken, suspend a 5 g weight at the free end of the membrane for 10 min and record whether the membrane remains intact.

[0048] 2. Experimental Data Table 2 3. Test Results As shown in Table 2, membranes G0, G1, G2, and G3 can all achieve self-healing in the hydrated state: the cut surfaces initially adhere at 5 minutes and are completely healed at 10 minutes, and after healing, they can withstand a 5g weight without breaking.

[0050] Example 3: Wet Adhesion Performance Test 1. Experimental Procedure Referring to the lap-shear test method in GB / T16777-2008 "Medical Flexible Polyvinyl Chloride Pipes and Fittings", fresh porcine uterine myometrial tissue (2 mm thick, cut into 2 cm × 1 cm rectangular blocks) was taken, and three parallel samples were prepared for each test. Hydrated membranes of G0, G1, G2, and G3 (cut into 1 cm × 1 cm squares, 0.5 mm thick) were sandwiched between two pieces of porcine uterine myometrial tissue, respectively, and a pressure of 50 kPa was applied and maintained for 10 min to ensure full adhesion between the membrane and the tissue. The peel force between the membrane and the tissue was tested using a universal testing machine (model: Instron5965) at a tensile speed of 5 mm / min. The adhesion strength was calculated according to the formula "Adhesion strength = Peel force / Adhesion area", and the average value of the three samples was taken.

[0051] 2. Experimental Data Table 3 3. Test Results As shown in Table 3, the wet adhesion strengths of G0, G1, G2, and G3 were 18.5 kPa, 18.2 kPa, 18.0 kPa, and 18.3 kPa, respectively, with no significant difference among the four (p>0.05), and all were significantly higher than those of the clinically commonly used Seprafilm (8.2 kPa). The wet adhesion properties of the four films were determined by the catechol groups of C-Gel (catechol binds to amino and thiol groups on the tissue surface after oxidation). The loading of siRNA nanocomposite did not affect the adhesion function of catechol, and all four films could adhere firmly to the moist wound surface.

[0053] Example 4: Degradation Performance Test 1. Experimental Procedure Take three dried membranes from each of G0, G1, G2, and G3, and weigh them (record as initial mass m0). Immerse each membrane in sterile PBS buffer (pH=7.4) containing hyaluronidase (10U / mL) and collagenase (5U / mL), and incubate in a 37℃ constant temperature water bath shaker (50rpm). After incubation for 7, 14, 21, and 28 days, remove the membranes, blot dry with sterile filter paper, and weigh them (record as mn). Calculate the degradation rate using the formula "degradation rate = (m0-mn) / m0×100%", and take the average value of the three groups of samples.

[0054] 2. Experimental Data Table 4

[0055] 3. Test Results As shown in Table 4, the degradation trends of G0, G1, G2, and G3 were consistent: approximately 35% degradation at 7 days, approximately 60% at 14 days, approximately 85% at 21 days, and complete degradation at 28 days. There was no significant difference in degradation rate among the groups (p>0.05). The degradation of the four membranes depended on the enzymatic hydrolysis of the matrix (hyaluronidase degrades A-HA, and collagenase degrades C-Gel). The loading of siRNA nanocomplexes did not change the enzymatic sensitivity of the matrix. The degradation cycle (28 days) of all four membranes matched the postoperative tissue repair cycle (2-4 weeks), eliminating the need for a second surgery to remove them.

[0056] Example 5: siRNA release assay 1. Experimental Procedure Take three dried membranes (G0, G1, G2, and G3, each containing approximately 1.18 μg of siRNA, calculated based on membrane volume and final siRNA concentration), and place them in centrifuge tubes containing 2 mL of sterile PBS buffer (pH=7.4). Incubate at 37°C. At 12 h, 24 h, 48 h, 7 days, 14 days, 21 days, and 28 days of incubation, aspirate 1 mL of supernatant (referred to as release solution) and add 1 mL of fresh PBS. Detect the siRNA concentration in the release solution using the RiboGreen method (ThermoFisher R11490 kit) with a fluorescence spectrophotometer (excitation wavelength 485 nm, emission wavelength 520 nm). Calculate the cumulative release rate using the formula: "Cumulative release rate = (total release at each time point) / initial total siRNA in the membrane × 100%", and take the average of the three groups.

[0057] 2. Test Results like Figure 3 As shown, the release trends of siTGF-β1 in G1 and G0 are consistent: rapid release within 48 hours, with a cumulative release rate of 55%-56%; release tends to level off after 7 days, and the cumulative release rate reaches over 95% after 28 days. The release trends of siSmad3 in G2 and G0 are consistent: slow release in the early stages, with a cumulative release rate of only 21%-22% after 48 hours; a cumulative release rate of 71%-72% after 14 days; and a cumulative release rate of over 91% after 28 days. In G0, the release of the two siRNAs does not interfere with each other, maintaining their respective release kinetic characteristics.

[0058] Both siRNAs in the G3 membrane exhibited a "rapid release" characteristic: the cumulative release rate reached 56%-57% at 48 hours and 72%-73% at 7 days, consistent with G1 (rapid release of siTGF-β1), and significantly different from siSmad3 (22.3% release at 48 hours) in G0 and siSmad3 (21.8% release at 48 hours) in G2. The release kinetics of siTGF-β1 and siSmad3 in the G3 membrane were almost identical, with no temporal difference, while a significant temporal difference existed between the two siRNAs in the G0 membrane (33.5% difference at 48 hours).

[0059] 3. Experimental Conclusions The release kinetics of siRNA are determined by the characteristics of the cationic polymers: the complex formed by LMWC (loaded with siTGF-β1) has a loose structure and is released rapidly; the complex formed by PEI (loaded with siSmad3) has a compact structure and is released slowly. All four membranes achieved the expected sequential release (G1 for rapid release of siTGF-β1, G2 for slow release of siSmad3, and G0 for dual sequential release), providing precise pharmacokinetic support for antifibrotic therapy.

[0060] The release kinetics of siRNA are determined by the vector characteristics: LMWC (loose complex) leads to rapid release, while PEI (tight complex) leads to slow release. The G3 membrane cannot achieve sequential release because both siRNAs are loaded with LMWC, while the G0 membrane, through the combination of "LMWC+PEI" vectors, successfully achieved the design goal of rapid release of siTGF-β1 and slow release of siSmad3, verifying the necessity of the sequential release system.

[0061] Example 6: Cytotoxicity test 1. Experimental Procedure Human uterine ligament fibroblasts (HULEC-5a) were cultured in DMEM medium containing 10% fetal bovine serum to the logarithmic growth phase. The cell concentration was adjusted to 5 × 10³ cells / well, and the cells were seeded into 96-well plates and incubated at 37°C and 5% CO2 for 24 h. Three dried membranes (0.1 g each) from G0, G1, G2, and G3 were taken and immersed in 10 mL of sterile DMEM medium, respectively, and incubated at 37°C and 5% CO2 for 24 h to prepare membrane extracts (concentration 10 mg / mL). The old medium in the 96-well plates was discarded, and 100 μL of DMEM medium was added to each well. LG0 extract, G1 extract, G2 extract, G3 extract, blank DMEM (negative control), and 10% DMSO (positive control) were used in 5 replicates per group. Incubation was continued for 24h, 48h, and 72h. 10 μL MTT solution (5 mg / mL) was added to each well. After 4h incubation, the supernatant was discarded, and 150 μL DDMSO was added to dissolve formazan crystals. The absorbance (OD value) was measured using a microplate reader (wavelength 570nm). Cell viability was calculated using the formula: "Cell viability = (OD value of experimental group / OD value of negative control group) × 100%".

[0062] 2. Experimental Data Table 5 3. Test Results As shown in Table 5, the extracts of G0, G1, G2, and G3 showed fibroblast survival rates ≥90% at 24h, 48h, and 72h, which were not significantly different from the negative control (p>0.05) and were much higher than the positive control (survival rate <16%). The matrix materials (A-HA, C-Gel) and cationic polymers (LMWC, PEI) of the four membranes were not cytotoxic, and the loading of siRNA did not introduce additional toxicity. All four membranes met the biosafety standards for medical materials.

[0064] Example 7: In vitro antifibrotic test 1. Experimental Procedure Take HULEC-5a cells and adjust the concentration to 2×10⁻⁶. 5Cells were seeded per well in 6-well plates and incubated at 37°C with 5% CO2 for 24 h. The old culture medium was discarded, and DMEM medium containing 10 ng / mL TGF-β1 (to induce fibrosis) was added. Simultaneously, G0, G1, G2, G3, and blank membrane extracts (blank control group) were added. Normal cell group (no TGF-β1, no extract) and model group (TGF-β1 only, no extract) were established, with 3 replicates per group. Incubation continued for 72 h. Total RNA was extracted from cells in each group using the Trizol method, and the RNA was reverse transcribed into cDNA using a reverse transcription kit. Using GAPDH as an internal control, the relative mRNA expression levels of fibrosis markers COL1A1 (collagen I gene) and ACTA2 (α-SMA gene) were detected using a qPCR kit (TaKaRaRR820A). Based on 2... ⁻ΔΔCt The relative expression level of mRNA was calculated using the method (with the normal cell group as 1), and the average value of the three groups of samples was taken.

[0065] The primer sequences are as follows: COL1A1-F: 5'-GAGGGCCAAGACGAAGACATC-3' COL1A1-R: 5'-CAGATCACGTCATCGCACAAC-3' ACTA2-F: 5'-GAGCGTGGCTATTCCTTCGT-3' ACTA2-R: 5'-TGGAAGGTAGACAGCGAAGG-3' GAPDH-F: 5'-CGCTTCTCTGCTCCTCCTGTTC-3' GAPDH-R: 5'-ATCCGTTGACTCCGACCTTCAC-3' In addition, total protein was extracted from cells in each group using RIPA lysis buffer (containing protease inhibitors), and protein concentration was determined using a BCA protein quantification kit (ThermoFisher 23225) to ensure consistent loading amounts (20 μg / lane) for each group. SDS-PAGE electrophoresis was performed (10% separating gel, 5% stacking gel), followed by electrophoresis at 80V for 30 min and then switching to 120V for 90 min. Protein was transferred to a PVDF membrane using a wet transfer method (300mA constant current, 90 min transfer time), and blocked with 5% skim milk for 2 h. Primary antibody (collagen I antibody: Abcam) was added. ab21286, dilution ratio 1:1000; α-SMA antibody: CST#19245, dilution ratio 1:1000; GAPDH antibody: CST#5174, dilution ratio 1:5000), incubated overnight at 4℃; added HRP-labeled secondary antibody (goat anti-rabbit IgG: CST#7074, dilution ratio 1:2000), incubated at room temperature for 1 h; developed using an ECL chemiluminescence kit (ThermoFisher32106), analyzed the band gray values ​​using ImageJ software, and calculated the relative expression level of the target protein with GAPDH as an internal control (with the normal cell group as 1).

[0066] The inhibition rate of each gene was calculated as follows: Inhibition rate (%) = (Expression level in the model group - Expression level in the treatment group) / (Expression level in the model group - Expression level in the normal group) × 100%.

[0067] 2. Test Results like Figure 4 As shown, the mRNA expression levels of COL1A1 and ACTA2 in the model group were significantly higher than those in the normal cell group (p<0.01), indicating that the fibrosis model was successfully constructed. There was no significant difference between the blank control group and the model group (p>0.05), indicating that the blank membrane had no anti-fibrotic effect. The mRNA expression levels of COL1A1 and ACTA2 in the G1 (single siTGF-β1) and G2 (single siSmad3) groups were significantly lower than those in the model group (p<0.01), with COL1A1 inhibition rates of 64.6% and 69.0%, and ACTA2 inhibition rates of 64.5% and 69.0%, respectively, indicating that the single siRNA-loaded membrane has a certain anti-fibrotic effect.

[0068] The expression levels of COL1A1 and ACTA2 mRNA in the G0 (dual siRNA) group were significantly lower than those in the G1 and G2 groups (p<0.01), with inhibition rates of 97.8% and 98.2%, respectively, approaching the levels of the normal cell group. This indicates that the synergistic inhibitory effect of dual siRNA far exceeds that of single siRNA. The inhibition rates of COL1A1 and ACTA2 mRNA in the G3 group (83.7% and 84.0%) were significantly higher than those in the G1 (64.6% and 64.5%) and G2 (69.0% and 69.0%) (p<0.01), indicating that dual siRNA still has a synergistic effect even without time-sequential release. However, the inhibition rate of the G3 group was significantly lower than that of the G0 group (97.8% and 98.2%) (p<0.01), with a difference of 14%-15%.

[0069] siTGF-β1 blocks the TGF-β1 / Smad pathway upstream at the mRNA level, while siSmad3 centrally blocks the TGF-β1 / Smad pathway at the mRNA level; the two work synergistically to inhibit the TGF-β1 / Smad pathway. A single siRNA can only partially inhibit the expression of fibrosis markers, while dual siRNAs, through dual blocking of the TGF-β1 / Smad pathway, almost completely inhibit the transcription of COL1A1 and ACTA2, providing a core molecular-level mechanism for anti-adhesion. In contrast, G3, due to the simultaneous rapid release of both siRNAs, resulted in insufficient Smad3 signal blocking in the later stages, leading to a weaker inhibitory effect than G0, thus validating the synergistic effect of the time-controlled release system.

[0070] The expression levels of collagen I and α-SMA proteins in the model group were significantly higher than those in the normal cell group (p<0.01), consistent with the trend at the mRNA level, further validating the successful construction of the fibrosis model. There was no significant difference in protein expression levels between the blank control group and the model group (p>0.05), again demonstrating that the blank membrane had no anti-fibrotic effect. The protein expression levels in the G1 and G2 groups were significantly lower than those in the model group (p<0.01), but higher than those in the G0 group (p<0.01), with collagen I inhibition rates of 64.2% and 68.9%, and α-SMA inhibition rates of 65.3% and 68.8%, respectively. The expression levels of collagen I and α-SMA proteins in the G0 group were extremely low, with inhibition rates of 97.6% and 98.1%, respectively, showing no significant difference from the normal cell group (p>0.05), fully validating the synergistic inhibitory effect at the protein level.

[0071] The protein inhibition rates of the G3 group (83.5%, 84.2%) were significantly higher than those of the G1 (64.2%, 65.3%) and G2 (68.9%, 68.8%) (p<0.01), but significantly lower than those of the G0 group (97.6%, 98.1%) (p<0.01). The trend of the protein inhibition rate was completely consistent with that of the mRNA level, further verifying the synergistic effect of time-sequential release.

[0072] The synergistic effect of dual siRNAs also holds true at the protein level, but sequential release (G0) can more thoroughly block the synthesis of fibrinogens: the sustained release of siSmad3 in the later stages of G0 can inhibit the downstream signaling of residual TGF-β1, while G3, due to the rapid release of siSmad3 in the early stages and insufficient concentration in the later stages, cannot sustainably block the signal, resulting in a weaker protein inhibitory effect than G0. Example 8: Inhibition of fibroblast migration - cell scratch assay 1. Experimental Procedure Take HULEC-5a cells and adjust the concentration to 5 × 10⁻⁶. 5 Cells were seeded per well in 6-well plates and incubated at 37°C with 5% CO2 until cell confluence reached 90% or higher. Using a sterile 200 μL pipette tip, a straight line (approximately 500 μm wide) was drawn in the center of the cell monolayer in each well. Cells were gently washed three times with PBS to remove floating cells. The cells were then divided into G0, G1, G2, G3 groups, a blank control group, a normal cell scratch group, and a model scratch group, with three replicates per group. Corresponding culture media (containing 10 ng / mL LGF-β1 and membrane extraction solutions) were added to each group, and normal cell scratch patterns were established. The model scratch group (without TGF-β1 and without extract) and the model scratch group (without TGF-β1 and without extract) were each set with 3 duplicate wells. At 0h, 12h, 24h and 48h after scratching, the scratch width was recorded by taking pictures in the same field of view (10× objective) using an inverted microscope (model: Olympus IX73). The scratch width was measured using ImageJ software, and the healing rate was calculated according to the formula "scratch healing rate = (0h scratch width - scratch width at each time point) / 0h scratch width × 100%". The average value of the 3 groups was taken.

[0073] 2. Test Results like Figure 5As shown, the healing rate of the model scratch group was significantly higher than that of the normal cell scratch group (p<0.01): the healing rate reached 85.0% at 24h and was almost completely healed at 48h, indicating that TGF-β1 can significantly promote fibroblast migration; there was no significant difference in the healing rate between the blank control scratch group and the model scratch group (p>0.05), indicating that the blank membrane could not inhibit fibroblast migration; the healing rates of the G1 and G2 scratch groups were significantly lower than those of the model scratch group (p<0.01), but higher than those of the G0 scratch group (p<0.01): at 24h The healing rates were 45.0% and 40.2% respectively, and the healing rates at 48 h were 75.2% and 70.5% respectively. The 24-hour wound healing rate of the G3 group (35.2%) was significantly lower than that of the G1 (45.0%) and G2 (40.2%) (p<0.01), but significantly higher than that of the G0 group (15.0%) (p<0.01). The 48-hour healing rate of the G3 group (60.1%) was consistent with that of the normal cell wound group (60.1%), while the 48-hour healing rate of the G0 group (30.5%) was only 50% of that of the normal cells. The healing rate of the G0 wound group was significantly lower than that of all other groups (p<0.01): the 24-hour healing rate was only 15.0%, and the 48-hour healing rate was only 30.5%, which was close to the migration speed of the normal cell wound group, indicating that the dual siRNA had a very strong inhibitory effect on fibroblast migration.

[0074] Fibroblast migration is a key step in postoperative adhesion formation (migrating to the wound and secreting collagen), and TGF-β1 can significantly accelerate this process. The G0 membrane, through the synergistic action of dual siRNAs, not only inhibits the expression of fibrosis markers but also strongly blocks fibroblast migration (inhibition rate of 82.4% at 24h), far exceeding the effect of a single siRNA membrane (G1 inhibition rate of 47.1% at 24h, G2 inhibition rate of 52.6% at 24h). This result demonstrates at the cellular behavior level that the G0 membrane can prevent adhesion by "reducing cell origin," complementing its inhibitory effect at the molecular level. Furthermore, due to insufficient siSmad3 concentration in the later stages, the migration rate of G3 returned to normal levels after 48h, further validating the crucial role of the time-controlled release system in maintaining a long-lasting anti-adhesion effect.

[0075] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A reabsorbable membrane for preventing adhesions after uterine fibroid surgery, characterized in that, It is prepared from raw materials containing the following components: Aldehyaluronic acid with an aldehyde degree of 15%-30%; Catechol-functionalized gelatin with a grafting rate of 8%-20%; A first nanocomposite formed by siRNA targeting the TGF-β1 gene and a first cationic polymer; A second nanocomposite formed by siRNA targeting the Smad3 gene and a second cationic polymer; In this process, aldehyde-modified hyaluronic acid with an aldehyde degree of 15%-30% and catechol-functionalized gelatin with a catechol grafting rate of 8%-20% form a dynamic covalent cross-linking network through the Schiff base reaction of aldehyde and amino groups, constituting the matrix of the membrane; the first nanocomposite and the second nanocomposite are embedded and fixed in the dynamic cross-linking network.

2. The absorbable anti-adhesion membrane after uterine fibroid surgery according to claim 1, characterized in that, The sense strand sequence of the siRNA targeting the TGF-β1 gene is SEQ ID NO:1, and the antisense strand sequence is SEQ ID NO:2; the sense strand sequence of the siRNA targeting the Smad3 gene is SEQ ID NO:3, and the antisense strand sequence is SEQ ID NO:

4.

3. The absorbable anti-adhesion membrane after uterine fibroid surgery according to claim 2, characterized in that, The first cationic polymer is a low molecular weight chitosan with a molecular weight ≤10kDa, and the mass ratio of siTGF-β1 to LMWC is 1:10 to 1:

50. The second cationic polymer is a branched polyethyleneimine with a molecular weight of 25 kDa, and the N / P ratio of siSmad3 to PEI is 5:1 to 15:

1.

4. The absorbable anti-adhesion membrane after uterine fibroid surgery according to claim 1, characterized in that, The aldehyde degree of the aldehyde-based hyaluronic acid is preferably 25%, and the catechol grafting rate of the catechol-functionalized gelatin is preferably 15%.

5. The absorbable anti-adhesion membrane after uterine fibroid surgery according to claim 1, characterized in that, The mass ratio of siTGF-β1 to LMWC is 1:20, and the N / P ratio of siSmad3 to PEI is 10:

1.

6. The absorbable anti-adhesion membrane after uterine fibroid surgery according to claim 1, characterized in that, The mass ratio of the siTGF-β1 / LMWC nanocomposite to the siSmad3 / PEI nanocomposite is 1:5 to 5:1, preferably 1:

1.

7. The absorbable anti-adhesion membrane after uterine fibroid surgery according to claim 1, characterized in that, The membrane has a porous structure with a pore size of 80-150 μm, a dry thickness of 0.2±0.05 mm, a hydrated thickness of 0.5±0.1 mm, a wet adhesion strength to porcine uterine myometrium of ≥15 kPa, and is completely degraded within 28 days in PBS containing hyaluronidase (10 U / mL) and collagenase (5 U / mL).

8. A method for preparing an absorbable anti-adhesion membrane after uterine fibroid surgery as described in any one of claims 1-7, characterized in that, Includes the following steps: Prepare aqueous solutions of aldehyde-modified hyaluronic acid and catechol-functionalized gelatin; A first nanocomposite was prepared by combining siRNA (siTGF-β1) targeting the TGF-β1 gene with a first cationic polymer; A second nanocomposite was prepared by combining siRNA (siSmad3) targeting the Smad3 gene with a second cationic polymer; Add the first nanocomposite and the second nanocomposite to the catechol-functionalized gelatin aqueous solution, and then mix with an equal volume of aldehyde-modified hyaluronic acid aqueous solution. Vortex the mixture to allow A-HA and C-Gel to undergo a Schiff base reaction through the aldehyde and amino groups. Pour the mixture into a mold and let it stand at 37°C for 15-30 minutes to form a hydrogel. The hydrogel can be freeze-dried to form the absorbable anti-adhesion membrane after uterine fibroid surgery.

9. The method according to claim 8, characterized in that, The concentration of the aldehyde-modified hyaluronic acid aqueous solution is 3%-6% (w / v), preferably 4% (w / v); The concentration of the catechol-functionalized gelatin aqueous solution is 3%-6% (w / v), preferably 4% (w / v); Add 10-20 μg / mL of the solution formed in the first nanocomposite and the second nanocomposite to the aqueous solution of the catechol-functionalized gelatin.